Indian Ocean regionalism: is there a future - Kelegama, Saman (2002)
The Indian Ocean Rim Association for Regional Cooperation was launched to affect a quicker process of liberalisation in countries disadvantaged in one way or other in the WTO regime, so that through open regional arrangements and agreements they could all gain quickly from the transforming trade and investment environment. An assessment of its five-year existance
Keywords: Indian Ocean Rim